ANALISIS FENOMENOLOGIS INTERPRETATIF REGULASI EMOSI GURU DALAM PENDIDIKAN HINDU NON FORMAL: PENGALAMAN SUBJEKTIF DI PRATAMA WIDYA PASRAMAN CAHAYA SARASWATI KABUPATEN KARANGANYAR - Riyadi, Agus; Wisnu Wardani, Dewi Ayu (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2025)
Emotional regulation is a crucial aspect of the teaching profession, particularly in a spiritually-based educational environment like the Pasraman (Islamic school). This study aims to explore teachers' subjective experiences in managing emotions while serving as educators at the Paratama Widya Pasraman Cahaya Saraswati in Karanganyar Regency. Using the Interpretative Phenomenological Analysis (IPA) method, data were collected from five teachers through participant observation, documentation, and in-depth interviews. Findings indicate that teachers' emotional regulation is grounded in Hindu values ​​such as satya (honesty), ksama (patience), and bhakti (spiritual devotion). Teachers view swadharma (sacred duty) as part of emotional awareness, which is carried out with spiritual awareness. Strategies used include spiritual reflection, self-control through japa (prayer), and a compassionate, dialogical approach. This study confirms that understanding emotional regulation in Hindu education is inseparable from the cultural and religious context. These findings contribute theoretically to discussions of emotions in alternative education and offer practical implications for teacher training that emphasizes spirituality and emotional well-being. Keywords: Emotional regulation, teachers, interpretive phenomenological analysis, Pasraman, Hindu education